Obsolescência do espaço: abordagem e compreensão dos vazios urbanos em Cachoeira do Sul - Moraes, Maicon Pinto de (2023)
The vacant urban space is a relevant element in the urban scenery because it is part of the Intra-Urban Open Spaces of the City, mostly of the times producing a negative impact and being an unproductive element for its environment. The search is focused on the analysis of the transformation of these residual spaces and built remnants of the decades of economic rise of Cachoeira do Sul, based on the problem of emergence and urbanization of these areas that have suffered from the emptying processes and its urban management, considering the impacts on its surroundings areas, both in landscape image and urban morphology. Three clippings were stipulated within the scope of the field of study, whose object of analysis is defined from: thematic clipping (vacant urban spaces and underutilized spaces); physical clipping (area of the study); and atemporal clipping (the situation of theses spaces today and its time marks). Through the conceptual framework and analysis of these urban voids in the cachoeira do Sul context, it was possible to categorize the urban voids of the city. Thus, all typologies found, a total of five, were spatialized in geoprocessing, with the aim of carrying out a morphological analysis of these spaces, especially with regard to their dispersion and occurrence in the urbanized area of the given city. As a way to complement the study, an online photoquestionnaire was also carried out, therefore, with the addition of the perception of the local population, the results obtained were valued. In advance, it can be stated that the urban voids of Cachoeira do Sul generally present a pattern of distribution across the territory, but when analyzed within their typologies, divergences are found in these configurations, where some categories form nuclei more concentrated and others maintain the tendency to spread. While some categories have a greater incidence on issues of proportions and area, others stand out across the population, either because of the aesthetics of dysfunction and emotion or because of the symbolic values they have. Thus, with the analysis of the results obtained, an overview of the phenomenon of urban voids in Cachoeira do Sul was drawn, in addition to the elaboration of strategies to face this problem that has been part of the urban reality of the city for some decades.